2017
DOI: 10.4049/jimmunol.1601643
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Changes in Bone Marrow Microenvironment Associated with Declining B Lymphopoiesis

Abstract: B lymphopoiesis arrests precipitously in rabbits such that by 2 to 4 months of age, prior to sexual maturity, little to no B lymphopoiesis occurs in the bone marrow (BM). Previously, we showed that in mice, adipocytes inhibit B lymphopoiesis in vitro by inducing inflammatory myeloid cells which produce IL-1β. Here, we characterized rabbit BM after the arrest of B lymphopoiesis and found a dramatic increase in fat, increased CD11b+ myeloid cells, and upregulated expression of the inflammatory molecules, IL-1β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 73 publications
4
27
0
Order By: Relevance
“…Similarly, H2-Ab1, H2-Eb1, and H2-Aa, which encode components of the major histocompatibility complex present on the surface of antigen-presenting cells, are negatively regulated, suggesting that immature B cells do not actively express these genes as much as mature B cells. We also found that S100a8, Betas, S100a9, Fos, and Camp are positively regulated in immature B cells; although these genes appear to be upregulated in a tissue-specific manner rather than in a cell type-specific manner, cytokines encoded by S100a8 and S100a9 were recently reported to regulate B lymphopoiesis in rabbit bone marrow [33]. Overall, our method detected reasonable DEGs in many cases; however, we could not find evidence implying the relationship between Malat1 (a long intergenic noncoding RNA) and B-cell development, and therefore, we hypothesize that this is a false positive due to its high variability regardless of cell type.…”
Section: Evaluation Of the Search Outcome And Deg Detectionsupporting
confidence: 54%
“…Similarly, H2-Ab1, H2-Eb1, and H2-Aa, which encode components of the major histocompatibility complex present on the surface of antigen-presenting cells, are negatively regulated, suggesting that immature B cells do not actively express these genes as much as mature B cells. We also found that S100a8, Betas, S100a9, Fos, and Camp are positively regulated in immature B cells; although these genes appear to be upregulated in a tissue-specific manner rather than in a cell type-specific manner, cytokines encoded by S100a8 and S100a9 were recently reported to regulate B lymphopoiesis in rabbit bone marrow [33]. Overall, our method detected reasonable DEGs in many cases; however, we could not find evidence implying the relationship between Malat1 (a long intergenic noncoding RNA) and B-cell development, and therefore, we hypothesize that this is a false positive due to its high variability regardless of cell type.…”
Section: Evaluation Of the Search Outcome And Deg Detectionsupporting
confidence: 54%
“…Similarly, H2-Ab1, H2-Eb1, and H2-Aa, which encode components of the major histocompatibility complex present on the surface of antigen-presenting cells, are negatively regulated, suggesting that immature B cells do not actively express these genes as much as mature B cells. We also found that S100a8, Beta-s, S100a9, Fos, and Camp are positively regulated in immature B cells; although these genes appear to be upregulated in a tissue-specific manner rather than in a cell type-specific manner, cytokines encoded by S100a8 and S100a9 were recently reported to regulate B lymphopoiesis in rabbit bone marrow [32]. Overall, our method detected reasonable DEGs in many cases; however, we could not find evidence implying the relationship between Malat1 (a long intergenic noncoding RNA) and B-cell development, and therefore, we hypothesize that this is a false positive due to its high variability regardless of cell type.…”
Section: Evaluation Of the Search Outcome And Deg Detectionsupporting
confidence: 52%
“…In mice fed a high-fat diet (HFD), early B cell development is characterized by decreased frequencies of B cell subsets in the bone marrow (BM) and reduced expression of early lymphoid commitment markers such as the B cell transcription factor PAX5 ( 44 ). Mechanistic experiments using co-cultures of BM cells with the OP9 stromal cell line have shown that BM adipocytes secrete soluble factors that drive the development of myeloid-derived suppressor cells (MDSCs) ( 45 , 46 ). MDSC inhibition of B lymphopoiesis is mediated by MDSC-derived IL-1β and the inflammatory molecule complex called calprotectin, suggesting that these may be therapeutic targets for the restoration of B lymphoiesis in obesity and aging.…”
Section: Effects Of Obesity On Mouse B Cellsmentioning
confidence: 99%